AKULTURASI BUDAYA ETNIS BELANDA DALAM MAKANAN NUSANTARA PERKEDEL - Riska Azikia Windiany; dinda reza okky naWa; Supriyono (Jurnal Budaya Nusantara, 2023)
Indonesia as a society is known for its cultural diversity such as traditional practices and customs. Some of them are historically influenced by colonialism. Just like Indonesia, which experienced a long colonial period under Dutch rule and left a big influence on aspects of people's lives and culinary delights in Indonesia. One of the Indonesian foods that were influenced by Dutch culture is Frikadeller. Frikadeller in Indonesia means "cakes" or fried potatoes and is usually bought and sold by fried traders or served as a complement to other foods. This study aims to analyze the influence of Dutch culture on Indonesian Frikadeller cuisine. Method: This research method is qualitative with data collection using literature studies and interviews regarding the history of Indo-Dutch food culture. Result: As a result of colonization, many Dutch tribes set foot in Indonesia, and the Dutch introduced cakes during their colonial period. Perkedel comes from the Dutch language, namely frikadeller, but the tongue of Indonesian people cannot pronounce the letter “f” so it becomes the letter “p”, and because the meat is expensive, until now perkedel is only made from potatoes. That's what makes frikadeller a potato-based cake.